Prolonged Infant Crying: Caregiving Quality and Child Physical Abuse Risk - Crouch, Julie L. (Journal of interpersonal violence, 2023)
Research suggests that prolonged infant crying may increase risk for child physical abuse (CPA). However, few studies have examined behavioral responses to infant crying among parents at risk for CPA. The present study sought to fill this gap by using a simulated infant to examine how mothers and fathers with varying degrees of CPA risk respond to prolonged infant crying. Specifically, a sample of 184 general population caregivers (107 mothers and 77 fathers) participated in a task that involved attempting to soothe a simulated infant that cried continuously for 30 min. The simulated infant sessions were video-recorded, and quality of caregiving behavior was coded in 5-min segments. Participants rated their negative affect (feelings of upset, distress, irritability) at the outset of the data collection session, before beginning the simulated infant task, and after the simulated infant task concluded. It was predicted that high-risk caregivers, compared to low-risk caregivers, would display lower quality caregiving, higher levels of negative affect, and that CPA risk group differences would increase over time. Gender differences were explored in relation to the aforementioned hypotheses. Over the course of the 30-min simulated infant task, the quality of caregiving behavior diminished among both high- and low-risk caregivers. As expected, high-risk caregivers, compared to low-risk caregivers, exhibited lower quality caregiving behaviors and were more likely to discontinue the simulated infant task early. In addition, high-risk, compared to low-risk, caregivers reported higher levels of negative affect throughout the data collection session, with the highest level of negative affect reported by high-risk caregivers after completing the simulated infant task. Overall, the quality of caregiving exhibited by men and women did not significantly differ. The present findings highlight the importance of early intervention designed to support caregivers’ abilities to respond effectively to prolonged infant crying.